Student career anxiety during the COVID-19 pandemic: A phenomenological exploration - Anita Budi Prabawaningrum; F. A. Nurdiyanto; Alyssa Berliana Putri; Enggar Putri Harjanti (HUMANITAS published by Universitas Ahmad Dahlan., 2023)
The COVID-19 pandemic has created a crisis in students' career development. Online learning activities could not have been optimal during the pandemic due to the poor quality of the internet network. Meanwhile, more than 1.2 million individuals had their employment terminated, resulting in their job loss. The pandemic contributes to students' career anxiety and mismatches in determining future careers. Our study explored the dynamics of student career anxiety that emerged during the COVID-19 pandemic through a phenomenological approach. Data was collected using semi-structured interviews by teleconference. The interviews focused on 1) how the participants experience career anxiety and 2) how it affects their career planning. Fifteen students participated through purposive sampling with criteria: 19-25 years old and undergraduate students. Interpretative Phenomenological Analysis (IPA) is applied as an analysis framework. We synthesized phenomenological themes identified as students' career anxiety: doubts about career plans, limited job opportunities due to the pandemic, and social comparison. The analysis also found that engaging in career-relevant communities was relevant to career readiness and deepening knowledge of career paths. This study encourages improving student skills by adjusting educational materials, training, or internships relevant to the student's potential and career needs during this critical time.